Egyetemi hallgatók mentális térképei Magyarországról - Kiss, János; Bajmócy, Péter (Tér és Társadalom, 1996)
What can we do, with the results of a mental-map analysis? What is the measurable benefit for a certain settlement? The answer we can give is clearer, more intelligible than in an average research. The analysis of the mental-maps can help the settlement, or a small region to make they character complete, to inform them about the opinions of the outside people, to make a realistic self-picture. The regional and settlement policy or the regional marketing, the development strategies functioning in a realistic space, in a space of the common verdicts and interests. The development srategy cannot based on an uncertain or a false picture. If the project based on a certain image analysis, completed with some objectiv facts (e.g. infrastructure, employment activity) the projects can be very efficient, make better results. It would be cheaper to change the mental views on the one hand, but they must draw the positive tendentions to the people’s attention. This process can help to enforce the favourable effects.